Determining the Source of Errors in a LEAN Cell Using RFID Technology - Lazarević, Milovan; Stankovski, Stevan; Ostojić, Gordana; Šenk, Ivana; Tarjan, Laslo (International Journal of Industrial Engineering and Management, 2013)
According to the LEAN philosophy, one of seven major losses incurred in the production process are errors in the quality. Any error in the products quality as a consequence has losses in the entire production process. Quick detection of the source of errors and causes of their occurrence are of vital importance for the management of production processes. With this aim, the paper proposes the use of RFID technologies to improve the monitoring of workers within the work cell. Under the proposed model, all activities of workers are collected and recorded independently or with very little involvement of workers. By analyzing the data collected, in addition to monitoring the activities of workers in terms of product quality, often other losses can also be identified according to the LEAN philosophy, such as over processing or waiting time, and thus affect their reduction or elimination from the production process. The results of applying RFID technology according to the above model are improved work processes in terms of efficiency and quality of working environment. Article history: Received (24.09.2012); Revised (15.04.2013); Accepted (28.06.2013)